(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2019)
To study the effect of small interfering RNA targeting metastasis-associated lung adenocarcinoma transcript1 (si-MALAT1) combining with curcumin on the invasion and migration abilities of human colon cancer SW480 cells, and to explore the involved molecular mechanism. The recombinant lentiviral vector expressing si-MALAT1 was constructed, and its titer was determined by gradient dilution method. The colon cancer SW480 cells with stable expression of si-MALAT1 was established, followed by treatment with curcumin at different concentrations. The effect of curcumin or si-MALAT1 alone and the combination of the two on the cell activity was detected by MTT assay. The cell invasion and migration abilities were detected by transwell and scratch-wound assay. The relative expression level of MALAT1 was detected by RT-qPCR. The protein expression was determined by Western blot analysis. The IC50 of curcumin alone was 77.69 µmol/L, which was 51.17 mol/Lwhen combined with curcumin and random sequence. The IC50 of curcumin was 30.02 µmol/L when combined with si-MALAT1. The increased susceptibility multiples was 2.58. The wound healing rates were 30.9% and 67.5% after treatment with si-MALAT1 combined with curcumin for 24 hrs and 48 hrs, respectively. The numbers of invasion cells were 200±12, 162±13, 66±8, 53±4 and 16±3 after treatment with si-MALAT1 combined with curcumin for 48 hrs. The relative expression level of lncRNA-MALAT1 in the curcumin group was 68%, and the relative expression level of lncRNA-MALAT1 in si-MALAT1group was 56%, and that for the combination treatment group was about 21%. The protein expression levels of β- catenin, c-myc and cyclinD1 were significantly down-regulated upon treatment with certain concentration of si-MALAT1 alone or combined with curcumin.si-MALAT1 could significantly inhibit the invasion and migration of SW480 cells by enhancing the sensitivity of SW480 cells to curcumin. The mechanism involved mignt be related to the down-regulation of β-catenin, c-myc and cyclinD1 proteins.